Esses cronistas de futebol e suas fábulas maravilhosas: a copa do mundo de 1998 na grande imprensa brasileira - Marques, José Carlos [UNESP] (My University, 2014)
This paper is focused on the reading of the texts of writers who collaborated with the leading newspapers of the Rio-São Paulo (represented here by the daily O Estado de S. Paulo, Folha de S. Paulo, O Globo and Jornal do Brasil) in coverage Football World Cup 1998, held in France. This tournament crystallized a growing trend from print to the Brazilian season: the convening of writers and chroniclers of notebooks from culture to comment on the matches of the World Cup. Here we analyze how these writers and their chronicles and columns permeated by the poetic and metalinguistic functions, enriched the sports pages with reports, stories or comments imagery, subjective and even fictional about football, a phenomenon that is countered, so the search for the referent and journalistic impartiality

Este ensaio está voltado à leitura dos textos de escritores que colaboraram com os principais jornais do eixo Rio-São Paulo (representados aqui pelos diários O Estado de S. Paulo, Folha de S. Paulo, O Globo e Jornal do Brasil) na cobertura da Copa do Mundo de Futebol de 1998, realizada na França. Esse torneio cristalizou uma tendência crescente do meio impresso brasileiro à época: a convocação de escritores e cronistas dos cadernos de cultura para comentar as partidas do Mundial. Analisamos aqui como as colunas e crônicas desses escritores, permeadas pelas funções metalinguística e poética, enriqueceram as páginas esportivas com relatos, narrativas ou comentários imagéticos, subjetivos e até mesmo ficcionais sobre o futebol, num fenômeno que se contrapôs, assim, à busca do referente e da isenção jornalística.
Soccer chroniclers and their wonderful tales: the 1998 world cup in the brazilian press
Keywords: World cup football 1998; Brazilian journalism; Literature; Copa do mundo de futebol de 1998; Jornalismo brasileiro; Literatura